(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Armina wattla Marcus and Marcus, 1967 and Armina abbotti Thompson, Cattaneo and Wong, 1990 were proposed by Ardila and Valdés (2004) to be junior synonyms of Armina muelleri (Ihering, 1886). A detailed anatomical review of these species (radula, reproductive system) and their distribution range revealed that A. wattla is a valid species and A. abbotti is a synonym of the former. Literature references to Armina tigrina Rafinesque, 1814 in the east coast of North America are misidentifications of some specimens of A. wattla.